A test of the Acoustic Adaptation Hypothesis in three types of tropical forest: degradation of male and female Rufous-and-white Wren songs. Issue 1 (2nd January 2017) - Graham, Brendan A.; Sandoval, Luis; Dabelsteen, Torben; Mennill, Daniel J.
Abstract: Many animals produce complex vocalizations that show pronounced variation between populations. The Acoustic Adaptation Hypothesis helps to explain this variation, suggesting that acoustic signals are optimized for transmission through different environments. Little is known about the transmission properties of female vocalizations because most studies of the Acoustic Adaptation Hypothesis have focused on male vocalizations of organisms living at temperate latitudes. We explored the relationship between environmental variation and the transmission properties of songs of Rufous-and-white Wrens, resident Neotropical songbirds where both sexes sing. Using playback, we broadcast and re-recorded elements of male and female songs from three populations of wrens living in three different forest habitats in Costa Rica. We measured four variables of the re-recorded sounds: signal-to-noise ratio, excess attenuation, tail-to-signal ratio and blur ratio. Our results show a significant difference between transmission characteristics of both male and female song elements across the three habitats, indicating that sounds transmit differently through different types of tropical forest. The population from which the broadcast sounds were recorded (source population) had little effect on sound transmission, however, suggesting that acoustic differences between these populations may not arise through acoustic adaptation to these habitats. Male and female elements showed similar transmission properties overall, although signal-to-noise ratio of male elements was influenced by source population, whereas blur ratio and excess attenuation of female elements were influenced by source population. Our study highlights the differences in transmission characteristics of animal sounds through different habitats, and reveals some sex differences in transmission properties.